Design of an RFID based Students/Employee Attendance System - OICC Press Authors (Majlesi Journal of Electrical Engineering)
The record of student attendance in most universities is done by calling the roll. This kind of calling is not only waste of class time, but also cannot be a true reflection of the real student attendance. The use of an alternative new system is becoming a mandate to manage students and staff attendance. The Radio Frequency Identification is the technology which will be applied as infrastructure in the indoor environment to enable the university management to take the advantages of its own and to enhance the university's monitoring system, taking into account factors such as reliability, time saving, and easy control. This paper automates the design and implementation of a studentsâ/employeesâ/lecturersâ attendance management system in terms of hardware and software in Al-Nahrain University in Baghdad. This system is named Al-Nahrain University Student Employee Attendance Management System (AUSEAMS). This system initially uses an RFID tagging system coupled with a web based database system to obtain complete system functionality where the information is manipulated in real time. Preliminary simulation results confirm the validity of the proposed system.